Teachers’ Perceptions of the Role of Universities in Mentoring Programs for Inclusive Elementary Schools: A Case Study in Indonesia - ., Rasmitadila; Humaira, Megan Asri; Rachmadtullah, Reza (Journal of Education and e-Learning Research, 2021)
The key problem with implementing inclusive education in inclusive elementary schools in Indonesia is that the role of all stakeholders in creating mentoring programs must be continuous and sustainable. The purpose of this study is to explore the opinions of general teachers (GTs) regarding the role of universities in mentoring programs for inclusive elementary schools. Data was collected using semi-structured interviews with 32 GTs in inclusive elementary schools. Data were analyzed using a thematic analysis of qualitative data. The results show two main themes, namely university involvement, and inclusive education resource centers. The roles of universities in mentoring programs for inclusive elementary schools are the development of effective instruction systems and the provision of human resources who are competent at implementing inclusive education in inclusive elementary schools. This research is expected to be the basis for policymakers, especially in universities, to design appropriate and relevant mentoring programs for the problems faced by inclusive elementary schools.